Penerapan Metode ROC-TOPSIS dalam Keputusan Penerima Program Keluarga Harapan - Hany Maria Valentine; Samuel Ramos; Fifto Nugroho; Mesran Mesran (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Poverty is one of the most difficult social problems to be solved by the Indonesian government, even in other words, the problem cannot be eliminated. So that the Indonesian government seeks to reduce the level of poverty by making social assistance programs to people who have economic problems. There are many aid programs set by the Indonesian government, one of which is the Family Hope Program (PKH). The Decision Support System is applied in this study as a system for the decision of the recipient of the family of hope. In determining the decision of the recipient of the right family program, it must meet the criteria for Poor Card Ownership, Employment, Income, Number of Dependents and Home Ownership Status. Therefore, a Decision Support System (DSS) is needed in solving existing problems by applying the ROC (Rank Order Centroid) and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) methods which can generate weight and preference values ​​from the first ranked alternative. . So that the recipient of the family of hope program lies in alternative A2 on behalf of Joko Sutirno with a value of 1.0000.